Audit Sistem Keamanan Informasi Menggunakan ISO 27001 pada SMKN 1 Pugung, Lampung: Audit Sistem Keamanan Informasi - Februari, Pangky; Fitria, Fitria (P3M Politeknik Negeri Banjarmasin, 2019)
The implementation of information and communication technology management has become a necessary in every educational institution, especially in SMKN 1 Pugung, Lampung. Hence, in this research is tried to measure the information security standard in SMKN 1 Pugung using ISO 27001. The method used is audit operational which relates with economical and efficiency used of resource as well as the target aimed. Afterwards, the result shows that the analysis of quisionnaire has obtained averages value amounts 3,32 in a whole ISO 27001. It means that information security standard has performed well and written operational procedure standard. Then, the evaluation result which varies from 11 clause I categorized into level 4 (manage and measurable). It means that business process has well-monitored and measured. So therefore, it can be concluded that system audit of security information in SMKN 1 Pugung has been confirmed as good enough.